2014
DOI: 10.1002/pat.3403
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐stabilized blue phases: promising mesophases for a new generation of liquid crystal displays

Abstract: Blue phases—special chiral liquid crystalline mesophases—are promising candidates for electro‐optic devices with improved performance and simplified fabrication. A necessary precondition for possible applications is a significantly enhanced temperature range of their existence, which can be achieved by a cross‐linked polymer network formed by in situ polymerization. Unlike many other mesophases, blue phases are optically isotropic if no voltage is applied. Regarding the transmission of a blue phase cell placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 162 publications
(432 reference statements)
1
19
0
Order By: Relevance
“…It is experimentally found that during cooling the existence of BPs has been observed in a wide temperature range about (9-15°C). This positive property can enable application of BPs in practice (for instance, for studies of colloidal particles in BPs [67] at nearroom temperature), as compared to the most wellknown pure thermotropic cholesterics and their mixtures, possessing BPs in narrow temperature ranges (0.5-2°C), that recently leaded to searches of new classes of the CLCs, possessing on the one hand, a wide temperature range of the blue phase, [40][41][42][43][44][45][46][47][48][49][50][51][52][53] in particular bimesogens, PS-BPLC or BPTN, [23,[25][26][27][28][29]33,39] and on the other hand CLCs, having BPs at low temperatures (i.e. at near-room temperature).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is experimentally found that during cooling the existence of BPs has been observed in a wide temperature range about (9-15°C). This positive property can enable application of BPs in practice (for instance, for studies of colloidal particles in BPs [67] at nearroom temperature), as compared to the most wellknown pure thermotropic cholesterics and their mixtures, possessing BPs in narrow temperature ranges (0.5-2°C), that recently leaded to searches of new classes of the CLCs, possessing on the one hand, a wide temperature range of the blue phase, [40][41][42][43][44][45][46][47][48][49][50][51][52][53] in particular bimesogens, PS-BPLC or BPTN, [23,[25][26][27][28][29]33,39] and on the other hand CLCs, having BPs at low temperatures (i.e. at near-room temperature).…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that the usage of PS-BPLCs is promising for photonics including 3D lasers, [24,[30][31][32] tunable gratings [34] and displays. [33,[35][36][37][38]44] A fast switching broad-temperature range electrooptical material was demonstrated in [39] for BPTN (by using available nematic LC MLC2048 and chiral dopant (ChD) S-811, further this template was filled with nematic E7). In addition, as shown in, [43,46] the doping of pure CLC CE6 (or CE8 [46]) with hydrophobic surface-treated CdSe nanoparticles can lead to an essentially stabilised BP-III (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to extend a temperature range of the BPLCs for practical applications, polymer networks are added to BPLCs to stabilize blue phase structure under temperature fluctuations which is also known as polymer-stabilized blue phase liquid crystals (PS-BPLCs) [7]. The PS-BPLCs with a broad temperature range greatly impact device applications [8,9], such as three dimensional mirror-less lasers [10], microlens arrays [11], Fabry Perot filters [12], a dye-doped polarizer-free display [13], variable optical attenuators [14], and grating [15]. However, hysteresis and uniformity hinder the development of PS-BPLC-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…Given the mature development of the operation modes for BP, many efforts were then shifted to embed BPLC in various display systems [86,137]. The research and development on BP based LCDs have been documented in detailed discussions [34,35,138,139].…”
Section: Optical Isotropy and Fast Electro-optic Responsementioning
confidence: 99%